Collective Remembering - Werts, James V. (Aurora. Revista de Arte, Mídia e Política, 2011)
“Collective memory” is a term widely used, yet difficult to define. Since the 1920s, when the father of modern collective memory studies, Maurice Halbwachs, published his seminal works on the topic, collective memory has surfaced occasionally as a topic of discussion in academic discussions, and it has long been discussed widely in public debate.